Impaired Lymphocyte Profile in Schistosomiasis Patients with Periportal Fibrosis - Luciana Santos Cardoso; Andréia de Souza Rocha Barreto; Jamille Souza Fernandes; Ricardo Riccio Oliveira; Robson da Paixão de Souza; Edgar M. Carvalho; Maria Ilma Araujo (Clinical and Developmental Immunology)
The Th2 immune response in chronic schistosomiasis is associated with the development of periportal fibrosis. However, little is known about the phenotype and activation status of T cells in the process. Objective. To evaluate the profile of T cells in schistosomiasis patients with periportal fibrosis. Methods. It was a cross-sectional study, conducted in the village of Agua Preta, Bahia, Brazil, which included 37 subjects with periportal fibrosis determined by ultrasound. Peripheral blood mononuclear cells were obtained by the Ficcol-hypaque gradient and the frequency of T cells expressing the surface markers CD28, CD69, CD25, and CTLA-4 was determined by flow cytometry. Results. The frequency of CD4+CD28+ T lymphocytes was higher in individuals with moderate to severe fibrosis compared to patients with incipient fibrosis. We did not observe any significant difference in the frequency of CD4+ T cells expressing CD69 among groups of individuals. There was also no significant difference in the frequency of CD8+ T cells expressing CD28 or CD69 among the studied groups. Individuals with moderate to severe fibrosis presented a lower frequency of CD8+ T cells, CD4+CD25high T cells, and CD4+CTLA-4+ T cells when compared to patients without fibrosis or incipient fibrosis. The frequency of CD4+CD25low cells did not differ between groups. Conclusion. The high frequency of activated T cells coinciding with a low frequency of putative Treg cells may account for the development of periportal fibrosis in human schistosomiasis.